2020
DOI: 10.1210/clinem/dgaa904
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Urinary and Serum Steroid Metabolites in Response to Testosterone Administration in Healthy Women

Abstract: Context Little is known about how exogenous testosterone (T) affects the steroid profile in women. More knowledge would give the antidoping community keys as to how to interpret tests and detect doping. Objective This work aimed to investigate the steroid profile in serum and urine in young healthy women after T administration. Methods In a randomized, double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…We, and others, have previously shown that implementation of the ABP increases the chance to detect testosterone intake in men as compared to traditional population based cut-off values after administration of low dose of testosterone (Strahm et al, 2015;Nair et al, 2020). Furthermore, in women the longitudinal ABP approach is superior to the population-based thresholds to detect administered T, however, not all women are identified as having atypical findings (Handelsman and Bermon, 2019;Knutsson et al, 2020;Salamin et al, 2020). It has been shown that after 10 weeks of transdermal T application in healthy women, only 40% were identified as having atypical passport findings (Knutsson et al, 2020) even though their serum T levels were elevated to concentrations associated with performance enhancing effects (Hirschberg et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We, and others, have previously shown that implementation of the ABP increases the chance to detect testosterone intake in men as compared to traditional population based cut-off values after administration of low dose of testosterone (Strahm et al, 2015;Nair et al, 2020). Furthermore, in women the longitudinal ABP approach is superior to the population-based thresholds to detect administered T, however, not all women are identified as having atypical findings (Handelsman and Bermon, 2019;Knutsson et al, 2020;Salamin et al, 2020). It has been shown that after 10 weeks of transdermal T application in healthy women, only 40% were identified as having atypical passport findings (Knutsson et al, 2020) even though their serum T levels were elevated to concentrations associated with performance enhancing effects (Hirschberg et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, in women the longitudinal ABP approach is superior to the population-based thresholds to detect administered T, however, not all women are identified as having atypical findings (Handelsman and Bermon, 2019;Knutsson et al, 2020;Salamin et al, 2020). It has been shown that after 10 weeks of transdermal T application in healthy women, only 40% were identified as having atypical passport findings (Knutsson et al, 2020) even though their serum T levels were elevated to concentrations associated with performance enhancing effects (Hirschberg et al, 2020). As a supplementary method, the serum concentration of T, androstenedione and dihydrotestosterone may be co-monitored (Salamin et al, 2020) and subsequently there is an interest to understand the relation between the serum steroid concentrations and urinary excretion rate of the ABP metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mullen et al [ 413 ] demonstrated that the variability of the ABP biomarkers in Swedish and Norwegian athletes was higher in females compared to males. Last, Knutsson et al [ 414 ] observed lower levels of E in PeO and higher levels of 5αAdiol in L in women with moderate to high self-reported levels of recreational physical activity.…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…The ADAMS platform indicated that 10 of the 11 passports were clearly suspicious, with most of the ratios exceeding the individual threshold. Knutsson et al [ 414 ] studied in 24 women the impact of 10 weeks of treatment with 10 mg testosterone cream and reported atypical results, mainly for the T/E ratio in 6 subjects, with only 2 subjects having an atypical 5αAdiol/E ratio [ 418 , 419 ]. Sometimes, athletes can only be tested once, and in such cases, the interpretation of a stand-alone data item can be complicated, especially for female athletes.…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…For the current sub-study, the urine samples of the last 50 participants were assayed for urinary testosterone at weeks 3, 6, 9, and 12. Urinary testosterone is recognized as a valid measure of testosterone production [ 17 ] that has been shown to correlate highly with serum testosterone levels following administration of exogenous testosterone in both young women ( r = 0.69) [ 18 ] and male athletes ( r = 0.56) [ 19 ]. The Research Ethics Board of the University of Regina approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%